Júlio de Mesquita Filho e o projeto de ensino superior paulista: seus escritos, sua atuação (1920-1938) - Santos, José Fagner Alves (2018)
This dissertation examines Júlio de Mesquita Filho's intellectual production and political performance (1892-1969) in the conduct of the debates that culminated in the creation of the University of São Paulo in 1934. The background and historical circumstances that were the scenario of intervention of groups in which and for which Mesquita Filho acted as protagonist. The project of higher education was investigated in the writings and speeches given, as a central category in the formation of intellectual cadres, especially in São Paulo, and the relations established by Júlio de Mesquita to consolidate what he defended for the future of São Paulo and the nation. The writings published in different spaces for the production of ideas, such as the newspaper O Estado de São Paulo, Revista do Brasil, among other vehicles - published before and after the creation of USP - are among the central sources of the present research, analyzed in the light of the intellectual and trajectory categories, among other concepts coming from the researches of Antonio Gramisci, J.F. Sirinelli and C. Charle